SEARCH FOR SPECTROSCOPIC FAMILIES AMONG DIFFUSE INTERSTELLAR BANDS - Wszolek, B.; Kuzmicz, A. (Одеські астрономічні публікації, 2010)
Diffuse interstellar bands (DIBs) await an explanation for many decades. One expects that significant progress in identification of DIBs’ carriers will be possible when all the known DIBs are divided into families in such a way that only one carrier is responsible for all bands belonging to the given family. Analysing high resolution optical spectra of reddened stars we test a new method to find out the first true spectroscopic families among DIBs.